(untitled) (Research, Society and Development, 2018)
The Supervised Curricular Internship is a mandatory and important step of the academic curriculum for teacher training. The course is not just another one in an undergraduate student program. For Pimenta (1995), it is an activity that allows students insertion - future teachers - in educational institutions, in other words, the insertion of future teachers into their workplace. Yet according to Pimenta, this inclusion will enable the undergraduate student to have a practical knowledge of how the teaching process is given. Not merely academically, but in the comprehension of this teaching process in its totally, in other words, the understanding of the teaching-learning process, the challenges, procedures to be followed, the obligations, everything that involves the teaching praxis in the real performance of the teacher. With this in mind, this research aims to analyze the foundation that regulates the Supervised Curricular Internship at “Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Norte” (IFRN). This analyzes are based on laws, opinions, and active normative acts about the internship and the professional experience of the undergraduate students. In addition, this research also analyzes the Didactic Organization (2012) of this institution concerning to the supervised internship of degree courses. Therefore, the documents analyzed in this paper reveal the importance a internship has in the training process, not as a required and isolated course, but rather as a prosecution of learning for the future teacher, in which theory and practice meet, allowing the undergraduate student their own experiences, being able to learn more with them.